Integrating Literacy and Numeracy Skills in Elementary Science and Social Studies Learning: A Framework Development Study - Ismail, Ali; Nugraha, Rana Gustian (Papanda Publisher, 2025)
This research developed and validated the Literacy and Numeracy Skill Development (LNSD) framework for integrating science and social studies (IPAS) instruction in elementary schools. Employing the 4D instructional design model (Define, Design, Development, Disseminate), the study systematically addressed the absence of pedagogical frameworks combining IPAS content with explicit literacy and numeracy skill development. The Define phase revealed through literature analysis and teacher interviews that existing IPAS instruction lacked systematic literacy-numeracy integration. The Design phase produced an initial framework adapted from Willison's Research Skill Development model, comprising distinct literacy and numeracy components with associated instructional sub-stages. The Development phase engaged three subject matter experts who validated the framework using Content Validity Index methodology, resulting in consensus on ten instructional sub-stages: four literacy components (Morning Message, Let's Read, Let's Write, Let's Practice) and six numeracy components (Read, Let's Compare, Let's Observe, Let's Try, Let's Practice, Reflection). The Disseminate phase implemented the validated framework with 18 sixth-grade elementary students in Garut Regency, Indonesia. Pre-test and post-test assessments demonstrated moderate effectiveness, with average scores increasing from 46.53 to 82.64 (gain = 36.1, N-Gain = 0.66). These findings confirm the framework's validity and effectiveness in simultaneously developing content understanding and foundational competencies, offering educators a systematic approach for integrated elementary instruction that addresses twenty-first-century learning demands.